FGFC1 overcomes Ara-C resistance in acute myeloid leukemia by inducing apoptosis and pyroptosis - Hu, Xiaohui; Li, Zhijian; Zhou, Rui; Zhang, Bing; Wang, Ruoxian; Li, Tongtong; Chang, Jiangcheng; Wu, Wenhui; Liu, Ning (Frontiers in Pharmacology, 2025)
Acute myeloid leukemia (AML) is a hematologic malignancy with a high mortality rate and poor prognosis, largely attributed to the emergence of chemotherapy resistance. Cytarabine (Ara-C), the cornerstone chemotherapeutic agent for AML, faces significant challenges due to the development of resistance, creating an urgent need for novel therapeutic strategies. Pyroptosis as a new form of programmed cell death has emerged as a potential therapeutic target in tumor treatment. However, its role in overcoming Ara-C resistance in AML by modulating pyroptosis remains unexplored. FGFC1 (Fungi fibrinolytic compound 1) a natural compound derived from Stachybotrys longispora FG216, has previously been shown to have high efficacy against erlotinib-resistant non-small cell lung cancer, yet its effects on AML are unknown. This study demonstrated that FGFC1 overcame Ara-C resistance in AML by inducing apoptosis and pyroptosis. Mechanistically, FGFC1 induced mitochondrial dysfunction and the accumulation of intracellular reactive oxygen species (ROS), leading to the release of cytochrome c (Cyto-C), which activated Caspase-3 and triggered both apoptosis and pyroptosis. This process was driven by inhibition of the PI3K/Akt/mTOR signaling cascade, ultimately suppressing the growth of AML Ara-C-resistant cells. These findings highlight the potential of FGFC1 to overcome Ara-C resistance in AML, providing a promising therapeutic strategy for drug-resistant AML and supporting the broader application of marine-derived small molecules in cancer therapy.